Lactic Acid Bacteria in Pharmaceutical Formulations: Presence and Viability of “Healthy Microorganisms” - Mariantonietta Succi; Elena Sorrentino; Tiziana Di Renzo; Patrizio Tremonte; Anna Reale; Luca Tipaldi; Gianfranco Pannella; Antonio Russo; Raffaele Coppola (Journal of Pharmacy and Nutrition Sciences, 2014)
Many probiotic formulations are available in the market and are advertised for several preventive or curative roles. The aim of this study was the identification of microorganisms composing different lactic acid bacteria based pharmaceutical formulations and the ascertainment of their ability to survive gastro-intestinal (GI) stresses, the main requisite to produce beneficial effects. For this purpose, viable bacteria were enumerated by plate counts in different media. Denaturing Gradient Gel Electrophoresis-Polymerase Chain Reaction (PCR-DGGE) analysis was applied on pure isolates and on crude formulations to confirm the composition in species. Also, crude formulations were subjected to stresses characteristic of the GI tract (GIT) to assess cell survival. Results highlighted concentrations lower than those reported in the labels in almost all the formulations. Moreover, some discrepancies were observed between reported species and those ascertained through the identification, and the use of an erroneous nomenclature was highlighted. The GI stress test revealed that bacteria are strongly injured, and this fact was evidenced by a marked reduction in viable counts after the stress. In conclusion, a widespread number of lactic acid bacteria based formulations are sold as probiotics, but their probiotic requisites are not adequately observed.